THE EFFECT OF LEADERSHIP STYLE AND SITUATION ON EMPLOYEE MOTIVATION AT PERUMDA AIR MINUM TIRTA JAYA MANDIRI, SUKABUMI REGENCY - CINDY NOVIANTY; DENI MUHAMMAD DANIAL; UNIN NIBI SAPUTRA (CV KULTURA DIGITAL MEDIA, 2021)
Leadership style and situation are assumed to influence employee motivation. There is a distinct challenge for a leader to adjust his leadership style and a good leadership situation so that employee motivation is well maintained in order to improve their performance. The research method was carried out by testing the associative correlation hypothesis with the product moment correlation test, single regression, and multiple regression (95% confidence level) with the help of the SPSS 25 program. The data were processed from 48 questionnaire answers from respondents. The results showed that there was a positive and significant relationship between leadership style and employee motivation, there was a positive and significant relationship between leadership situation and employee motivation, there was no positive and significant relationship between leadership situation and leadership style, there was a positive and significant relationship. between leadership style and leadership situation together on employee work motivation